Assessing national achievement levels in education - 4 0 16; Greaney, Vincent.;Kellaghan, Thomas; 5 (Washington, DC : World Bank, 2008)
Describes the importance of national assessment in education, and discusses methods to define levels of achievement in key subject areas and subgroups--boys and girls, ethnic groups, rural and urban students, and more--and explores issues that relate to design, implementation, analysis, and reports.
Includes bibliographical references (p. 145-154) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Educational tests and measurements.;Educational evaluation.;Educational tests and measurements.;Educational evaluation; 20; 2